Molecular characterization of a bactericidal permeability-increasing protein/lipopolysaccharide-binding protein from black rockfish (Sebastes schlegelii): Deciphering its putative antibacterial role. (February 2017) - Lee, Seongdo; Elvitigala, Don Anushka Sandaruwan; Lee, Sukkyoung; Kim, Hyun Chul; Park, Hae-Chul; Lee, Jehee
Abstract: Bactericidal permeability-increasing protein (BPI)/lipopolysaccharide (LPS) binding proteins (LBPs) are well-known proteins that play an indispensable role in host antimicrobial defense. Herein, we report a homolog of BPI/LBP from black rockfish ( Sebastes schlegelii ) (designated as RfBPI/LBP) and characterize its structural and functional features at the molecular level. We identified the putative complete open reading frame (1422 bp) of RfLBP that encodes a 474 amino acid protein with a predicted molecular mass of ∼51.5 kDa. The primary protein sequence of RfBPI/LBP contains domain features of BPI/LBP family proteins and shares significant sequence consistency with its homologs. Our phylogenetic analysis clearly demonstrated the vertebrate ancestral origin of RfBPI/LBP, further reinforcing its evolutionary relationship with teleostean homologs. Recombinant RfBPI/LBP demonstrated in vitro LPS-binding activity and antibacterial activity against Escherichia coli, but not against Streptococcus iniae . Moreover, RfBPI/LBP exhibited temporal transcriptional activation against pathogens and pathogen-associated molecular patterns. Collectively, our findings suggest that RfBPI/LBP plays an essential role in host antimicrobial defense, plausibly through selective eradication of invading bacteria. Highlights: Homolog of BPI/LBP was identified from black rockfish (RfBPI/LBP). Rf RfBPI/LBP resembled typical domain architecture of its homologues. Recombinant RfBPI/LBP showed selective antibacterial and LPS binding activity. RfBPI/LBP was ubiquitously expressed in tissues under physiological conditions. Transcriptional level of RfBPI/LBP was modulated under pathogenic stress.